2015
DOI: 10.1038/nrm3934
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal regulation of the anaphase-promoting complex in mitosis

Abstract: The appropriate timing of events that lead to chromosome segregation during mitosis and cytokinesis is essential to prevent aneuploidy, and defects in these processes can contribute to tumorigenesis. Key mitotic regulators are controlled through ubiquitylation and proteasome-mediated degradation. The Anaphase-Promoting Complex or Cyclosome (APC/C) is an E3 ubiquitin ligase that has a crucial function in the regulation of the mitotic cell cycle, particularly at the onset of anaphase and during mitotic exit. Co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
271
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(275 citation statements)
references
References 199 publications
(309 reference statements)
2
271
0
2
Order By: Relevance
“…6B). APC/C is a positive regulator of mitosis and functions as an E3 ubiquitin ligase to mark cell cyclerelated proteins for proteasomal degradation (22). Loss of APC/C results in cell cycle arrest at metaphase and severe aberrations of the mitotic spindle (23).…”
Section: Kpnb1 Positively Regulates Members Of the Anaphase-promotingmentioning
confidence: 99%
“…6B). APC/C is a positive regulator of mitosis and functions as an E3 ubiquitin ligase to mark cell cyclerelated proteins for proteasomal degradation (22). Loss of APC/C results in cell cycle arrest at metaphase and severe aberrations of the mitotic spindle (23).…”
Section: Kpnb1 Positively Regulates Members Of the Anaphase-promotingmentioning
confidence: 99%
“…This bipolar kinetochore-microtubule attachment enables all sister chromatids to align at the metaphase plate. The anaphase-promoting complex or cyclosome (APC/C), along with its activator cell division cycle 20 (Cdc20), indirectly activates the protease separase through triggering the ubiquitination and degradation of the separase inhibitors, securin and cyclin B1 (3)(4)(5). Active separase then cleaves cohesin, leading to chromosome segregation (6,7).…”
mentioning
confidence: 99%
“…During spindle checkpoint signaling, the mitotic checkpoint complex (a complex of Bub3, Mad2, and Mad3) prevents APC/C Cdc20 from ubiquitinating its substrates, however, APC/ C Cdc20 is still active to auto-ubiquitinate Cdc20. 3 An in vitro study showed that during checkpoint activation, Bub3 promotes the binding of Cdc20 and APC/C for its auto-ubiquitination. 1 We propose a model in which kinetochore localized Bub3 facilitates the binding of Cdc20 and the APC/C in metaphase.…”
mentioning
confidence: 99%
“…For the onset of anaphase, the APC/C binds its co-activator Cdc20 and targets substrates for ubiquitination and proteasomal degradation. 3 One substrate, securin, binds and inhibits separase, a protease that cleaves cohesin. The degradation of securin releases separase, promoting sister chromatid separation and anaphase onset.…”
mentioning
confidence: 99%